Characterization of microsatellite loci in Himatanthus drasticus (Apocynaceae), a medicinal plant from the Brazilian savanna - Baldauf, Cristina; Ciampi, Maísa B.; Vigna, Bianca B. Z.; Mori, Gustavo M.; Guedes, Julian P. P.; De Souza, Anete P.; Santos, Flavio A. M. dos (American journal of botany, 2011)
• Premise of the study: We developed a new set of microsatellite markers for studying the genome of the janaguba tree, Himatanthus drasticus (Mart.) Plumel, which is used in folk medicine in northeastern Brazil. These novel markers are being used to evaluate the effect of harvesting on the genetic structure and diversity of natural populations of this species. • Methods and Results: Microsatellite loci were isolated from an enriched H. drasticus genomic library. Nine primer pairs successfully amplified polymorphic microsatellite regions, with an average of 8.5 alleles per locus. The average values of observed and expected heterozygosity were 0.456 and 0.601, respectively. • Conclusions: The microsatellite markers described here are valuable tools for population genetics studies of H. drasticus. The majority of the primers also amplified sequences in the genome of another species of the same genus. This new set of markers may be useful in designing a genetic conservation strategy and a sustainable management plan for the species.